2012
DOI: 10.1186/1743-7075-9-30
|View full text |Cite
|
Sign up to set email alerts
|

Chromium picolinate and chromium histidinate protects against renal dysfunction by modulation of NF-κB pathway in high-fat diet fed and Streptozotocin-induced diabetic rats

Abstract: BackgroundDiabetic nephropathy is one of major complications of diabetes mellitus. Although chromium is an essential element for carbohydrate and lipid metabolism, its effects on diabetic nephropathy are not well understood. The present study was conducted to investigate the effects of chromium picolinate (CrPic) and chromium histidinate (CrHis) on nuclear factor-kappa B (NF-κB) and nuclear factor-E2-related factor-2 (Nrf2) pathway in the rat kidney.MethodsMale Wistar rats were divided into six groups. Group I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…For above reasons, some organic trivalent chromium compounds such as chromium(III) picolinate (CrPic) have been used as nutritional supplement for providing Cr(III) to human since the CrPic has low toxicity and high bioavailability . Some studies have shown that CrPic has a protective role against diabetic nephropathy and exerts antidiabetic activities, although these results are disputed . On the other hand, Cr(VI) is considered to be extremely toxic to organism since it has strong mutagenic and carcinogenic effects .…”
Section: Introductionmentioning
confidence: 99%
“…For above reasons, some organic trivalent chromium compounds such as chromium(III) picolinate (CrPic) have been used as nutritional supplement for providing Cr(III) to human since the CrPic has low toxicity and high bioavailability . Some studies have shown that CrPic has a protective role against diabetic nephropathy and exerts antidiabetic activities, although these results are disputed . On the other hand, Cr(VI) is considered to be extremely toxic to organism since it has strong mutagenic and carcinogenic effects .…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent chromium is an essential trace metal that has been shown to lower oxidative stress and improve glucose and lipid metabolism (29)(30)(31)(32)(33)(34)(35). Chromium picolinate Cr(pic)3 is a widely consumed and well absorbed form of trivalent chromium that is widely promoted as a dietary supplement for adjunctive therapy for Type 2 diabetes (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…Chromium picolinate Cr(pic)3 is a widely consumed and well absorbed form of trivalent chromium that is widely promoted as a dietary supplement for adjunctive therapy for Type 2 diabetes (29,30). Cr(pic)3 supplementation has the potential to reduce cellular oxidative stress (30,31), levels of proinflammatory cytokines (32)(33)(34), blood cholesterol and triglycerides in diabetes (26,32). Whereas Cr(pic)3 has been extensively investigated in relation to carbohydrate and lipid metabolism, there are only a few studies devoted to the effects of Cr (pic)3 on the cardiovascular system (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…DN was considered as a major complication of diabetes in global population (Kelly et al., ) and its development, management, and prevention were regulated by nutrition and diet (Selcuk et al., ). Obesity‐ and/or diabetes‐induced hyperglycemia is the main key factor for the development and progression of DN, which activates the various signaling pathways such as polyol, hexosamine, NF‐kB, AGE, PKC, Bax/Bcl‐2, and other pathways via ROS generation and lead to the insulin resistance associated with renal damage (Haq, Banday, & Bashir, ).…”
Section: Discussionmentioning
confidence: 99%